Geometric progression (g.p.), Mathematics

Learning geometric progression vis-á-vis arithmetic progression should make it easier. In geometric progression also we denote the first term by 'a' but a  basic difference from A.P. is that instead of common difference we have common ratio 'r'. Like d, r remains constant whenever the ratio of any two consecutive terms is computed. The terms of a G.P. are

                   a, ar, ar2, ar3, ar4, ................, arn - 1  

That is,         T1     =     a

                   T2     =     ar

                   T3     =     ar2

                   :                :
                   :                :

                   Tn     =     arn - 1

This is similar to A.P. We take an example to become more familiar with this.

Example 

It is known that the first term in G.P. is 3 and the common ratio r is 2. Find the first three terms of this series and also the nth term.

We know that the first term is given by

                   T1     = a   = 3

                   T2     = ar   = 3.2     = 6

                   T3     = ar2  = 3.2.2 = 12

The nth term is given by  Tn  = arn-1  = 3(2)n-1

Posted Date: 9/13/2012 4:26:09 AM | Location : United States







Related Discussions:- Geometric progression (g.p.), Assignment Help, Ask Question on Geometric progression (g.p.), Get Answer, Expert's Help, Geometric progression (g.p.) Discussions

Write discussion on Geometric progression (g.p.)
Your posts are moderated
Related Questions

robin runs 5 kilometers around the campus in the same length of time as he can walk 3 kilometers from his house to school. If he runs 4 kilometers per hour faster than he walks, ho


Find out the surface area of the solid acquired by rotating y = √ (9-x 2 ), - 2 x 2 about the x-axis. Solution The formula that we'll be using here is, S = ∫ 2Πyds

We have to enclose a field along with a fence. We contain 500 feet of fencing material & a building is on one side of the field & thus won't require any fencing.  Find out the dime

Example of Linear Equations: Solve the equation 2x + 9 = 3(x + 4). Solution: Step 1. Using Axiom 2, subtract 3x and 9 from both sides of the equation. 2x + 9 = 3(

(-85) from (-21) and explain me

1. Consider the following context free grammar G with start symbol S (we write E for the empty string, epsilon): S ---> bB | aSS A ---> aB | bAA B ---> E | bA | aS a. D